1991
DOI: 10.2307/2048410
|View full text |Cite
|
Sign up to set email alerts
|

On a Singular Nonlinear Elliptic Boundary-Value Problem

Abstract: Abstract.We consider the singular boundary-value problem Au+p(x)u~7 = 0 in d, u | 9Í2 = 0 , where y > 0 . Under the assumption p(x) > 0 and certain smoothness assumptions, we show that there exists a solution which is smooth on £2 and continuous on Í2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 3 publications
(4 reference statements)
2
127
0
Order By: Relevance
“…[5,7,8,11,12] and their references). For bounded Ω, in [7] it is shown that Problem (2) with 0 < γ < 1 has a unique positive weakly solution in…”
Section: Introductionmentioning
confidence: 99%
“…[5,7,8,11,12] and their references). For bounded Ω, in [7] it is shown that Problem (2) with 0 < γ < 1 has a unique positive weakly solution in…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to check that M ϕ 2−a 1 is a supersolution of (15) while the zero function is a subsolution. This simple observation together with the maximum principle yield the existence and uniqueness of a solutionw ∈ C 2 (Ω) ∩ C(Ω) of (15). By Lemma 2.3 we havew…”
Section: Some Preliminary Resultsmentioning
confidence: 63%
“…which was considered, among other works, in [3,9,15]. A particular feature of (2) in the case p > 0, and in contrast to the case p < −1 is that it has a unique solution.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Before we explore this crucial issue, let us pause to comment on the boundary behavior of u as a function of γ for p(x) uniformly positive; u is smooth in the interior of Ω, depending on the regularity of p. Lazer and McKenna [16] show the following facts:…”
Section: Smooth Nonlinearitymentioning
confidence: 99%